Adoption of Financial Technology (FinTech) Services for Iraqi Bank Users: an extension of technology acceptance model - Sahi, Alaa Mahdi (Universitas Sang Bumi Ruwa Jurai, 2024)
The study aims to explore the determinants of Financial Technology adoption among Iraqi bank users. Building on the Technology Acceptance Model, the study integrates Perceived Economic Wellbeing and Digital Literacy with traditional TAM constructs including Perceived Ease of Use, Perceived Usefulness, and Subjective Norms. The data were collected through a survey methodology which included banking clients in Iraq. A total of 280 bank customers contributed to the research, yielding a response rate of 93.33%. Hypotheses were tested using Structural Equation Modelling (SEM). The findings suggest that perceived usefulness, ease of use, subjective norms, and digital literacy are instrumental in adoption FinTech services. On the other hand, economic well-being has no significant impact. This implies that digital literacy and social influence exert a significant effect on FinTech acceptance by users in developing countries. The study will be useful for policy makers and the management of financial institutions aiming to enhance FinTech adoption through policies aimed to improve users’ perceptions of usefulness and ease-of-use as well as to develop users’ digital literacy. The study contributes to the existing literature limited literature on FinTech adoption in the Arab world, particularly Iraq